Asuhan Kebidanan Pada Ibu Nifas Dengan Puting Susu Terbenam Grade II Di PMB Nislawaty Wilayah Kerja Puskesmas Bangkinang Kota Tahun 2024 - Angelita, Dea; Nislawaty, Nislawaty; Lubis, Dumasari (Evidence Midwifery Journal, 2024)
Immersed nipples are nipples that cannot protrude and are pulled inward, which results in the milk not coming out smoothly due to shorter inward milk ducts (tied nipples), lack of early breast care, and the mother's lack of knowledge regarding breast care. Inverted nipples are divided into 3 grades. The care provided is in accordance with the grade of nipple immersion. The aim of the research is to provide midwifery care to postpartum mothers with grade II inverted nipples at the Nislawaty Independent Midwife Practice (PMB) in the Bangkinang City Community Health Center Work Area on 08-14 May 2024. The results of the case study research found that Mrs. C experienced inverted nipples grade II. Care was carried out seven times at home during 1 week. Midwifery care is provided in the form of counseling to mothers regarding inverted nipples, teaching mothers how to deal with inverted nipples using a syringe and the Hoffman technique, as well as teaching mothers breast care techniques. Based on the postpartum care provided to Mrs. C aged 25 years P1A0 found that the inverted nipples were starting to stand out. The conclusion is that the care provided was carried out well and produced positive results. It is hoped that this research can serve as a reference, add to discourse, and develop knowledge regarding midwifery care for postpartum mothers with grade II inverted nipples.